PS-014 An observational review and audit of the treatment of hypoglycaemic events in a university teaching hospital. (25th February 2017) - Molony, S; McCabe, L; Mcquaid, S; Kieran, M; Meegan, C
Abstract : Background: Hypoglycaemic events may have grave implications for patients with diabetes mellitus, and is defined as a blood glucose (BG) level of <4 mmol/L. Anecdotally, it has been reported that events were not treated as per evidence base in the hospital setting. Purpose: This study aimed to conduct a baseline audit and review of the treatment of hypoglycaemic events among diabetic inpatients in a university teaching hospital. Quality improvement methods and a reaudit were also planned. Material and methods: Baseline adherence to the hypoglycaemic hospital protocol was determined in an audit undertaken on 148 retrospective hypoglycaemic events, by clinical pharmacists, over a 5 week period. Data were analysed and quality improvement initiatives were implemented by the pharmacy department in conjunction with the endocrinology department. The efforts employed included the development and launch of a new hypoglycaemia protocol, the provision of educational material in the form of a quiz, a medication safety alert, and informal and formal education. A reaudit was undertaken over a 5 week period on 151 hypoglycaemic events. Results: 72.9% (n=108) of hypoglycaemic events in the baseline audit were treated with short acting carbohydrate, which increased to 81.4% (n=123) in the reaudit (p>0.05). Lucozade was the predominant short acting carbohydrate used to treat hypoglycaemic events throughout the study. Of those events treated with Lucozade, 33.3% were treated with the recommended amount in the baseline audit, increasing to 70.6% in the reaudit (p<0.05). There was limited compliance with retesting of BG within 15 min in the baseline audit (repeated within 15 min in 9.5%; within 30 min in 24.8%). The time to retest was significantly reduced (p<0.05) in the reaudit (BG repeated within 15 min in 30.5%; within 30 min in 63.5% of events). Conclusion: We established the baseline incidence of hypoglycaemic events. With the provision of a clear, colour coded evidence based hypoglycaemia protocol and a multifaceted educational drive, it was possible to improve the management of these hypoglycaemic events to improve patient safety. References and/or acknowledgements: 1. Joint British Society for Diabetes. The hospital management of hypoglycaemia in adults with diabetes mellitus . cited 14 Sep 2014. Available at https://www.diabetes.org.uk/ No conflict of interest